Assessment of Knowledge, Attitude, and Practice of Obstetricians and Gynecologists Toward Off-Label Medicine Use in Female Reproductive Health Issues - Shakeel, Sadia; Iffat, Wajiha; Qamar, Ambreen; Nesar, Shagufta; Butt, Fareeha; Siddiqui, Sobia Naseem; Rehman, Hina; Rehman, Anees ur (Frontiers in Public Health, 2022)
Background Off-label medication usage (OLMU) is prevalent in the treatment of various diseases, including female reproductive health issues (FRHIs). However, there is a paucity of literature on the perspective of health professionals on this subject. The purpose of the current study was to assess gynecologists/obstetricians' knowledge, attitude and practice toward OLMU in the treatment of FRHIs. Methods The current cross-sectional study was conducted in September and October 2021, at five tertiary care hospitals (two public and three private sector), different clinics and maternity homes in a metropolitan city of Karachi, Pakistan. The target population was gynecologists, obstetricians and physicians/residents working in the ob/gyn department in various hospitals and clinical settings of Karachi. Results The overall response rate was 77.1%. The mean age of the study respondents was 36.1 ± 7.7 years; n = 85 (55.9%) respondents were working in primary patient care. The majorly reported OLMU by the respondents were clomiphene citrate in unexplained infertility (n = 66; 43.4%), metformin to improve cycle regularity in females with polycystic ovary syndrome (PCOS) (n = 59; 38.8%) and letrozole to induce ovulation (n = 31; 20.4%). The majorly stated categories of OLMU were at a different dose (n = 95; 62.5%) and at different indications than approved to treat (n = 89; 58.5%). It was reported by the majority of the respondents (n = 95; 62.5%) that they do not follow any guidelines or regulations for OLMU in their work setting; however, the response was statistically varied with the working organization (CI 2.14–2.93; p = 0.037) and practice area (CI 2.85–4.32; p = 0.0001) of respondents. Conclusions The present study revealed that the respondents were well-familiar with the practice of OLMU in the treatment of FRHIs. They expressed their concerns about decreasing such practices by being involved in collective decision-making procedures, and they were inclined to accept initiatives aimed at ensuring drug safety in patients.